Holistic Healing: How Homeopathy Supports Women with Ovarian Endometrioma (Homoeopathy for All, 2025)
Endometrial tissue implantation in the  ovaries causes ovarian endometrioma,  a benign but difficult disorder that  affects women of reproductive age.  Its epidemiology, etiology, risk  factors, clinical manifestation, and  diagnostic techniques are all examined  in this article. Hormonal medication  and surgery are the mainstays  of conventional medicine, but  homeopathy provides a comprehensive,  non-invasive substitute. This article  discusses the therapeutic indications of  15 important homeopathic treatments  for ovarian endometrioma as well as an  integrative therapy strategy.
Keywords: Ovarian endometrioma; Chocolate cyst